THE INFLUENCE OF INFLATION AND DEBT ON FIRM VALUE IN FOOD AND BEVERAGES COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) - Faradina Khairunnisa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to provide evidence related to the influence of inflation and debt on firm value. Population used in this research is 14 food and beverages companies from IDX. The research uses purposive sampling method for selecting the samples resulted 12 qualified companies during 2011-2014. Inflation is measured using the consumer price index released by the World Bank. Debt is measured using debt to equity ratio, and firm value is measured using tobins’ q. The data analysis is conducted using multiple regression analysis. Test result shows that inflation has no influence on firm value, since food and beverages companies is categorized as consumer staples, which refers to a business comprised of those companies, which sell the basic human needs. Meanwhile, debt has a significant influence on firm value because the selected companies can achieve optimal capital structure by using trade-off theory to maximize the value of the firm by balancing the costs and benefits of an additional unit of debt.Keywords: inflation, debt, firm value.